The Development of Small Medium Enterprises and their impact to the Ghanaian Economy - Hayford, Sydney (2013)
A thesis submitted to the Institute of Distance Learning, Kwame Nkrumah University of Science and Technology in partial fulfilment of the requirement for the degree of MASTERS IN BUSINESS ADMINISTRATION Commonwealth Executive Masters in Business Administration, Institute of Distance Learning